Preparing the PPP phoenix to fly: Redesigning frameworks to match emerging vistas - Prateek Kumar; Gupta, Roopali (2016)
In the wake of falling interest of the private sector in taking public projects due to high risk and limited availability of debt finance, and keeping in view the impossibility of meeting the infrastructure gap of India without private participation, this article aims at finding the flaws of the current PPP framework and suggesting amendments to match the challenge of crowding-in private investments for public projects. This article discusses various models and mechanisms for achieving sustainable and cost-efficient 'project finance' or 'funding structures' and highlights government schemes that have enabled or incentivised the usage of new financing options. It critically examines the various drawbacks present in the existing PPP framework and evaluates and makes detailed suggestions on the structural changes required in it to make it attractive to investors and successful in results. It also evaluates the changes brought and proposed in the PPP framework such as 'plug-and-play' mode, the Swiss Challenge Method, and Hybrid Annuity Model. The public-private-people-partnership or 4P model is given not only in its theoretical context but also in its functional sense by graphic representation of the framework and by taking examples of new government initiatives in this direction. - Reproduced.
Keywords: Public private partnerships